Assessment of Interobserver Variability for CT Scan–Based Evaluation of Posterior Ligament Complex Injury in Thoracolumbar Fractures: An International Multicenter Pilot Study. Issue 2 (April 2020) - Maheswaran, Anupama; Aiyer, Siddharth N.; Farouk, Osama; El-Sharkawi, Mohammad; Park, Jong-Beom; O'Brien, Andrew; Oluwole, Ige; Wang, Yue; Arruda, André de Oliveira; Rajasekaran, Shanmuganathan
Study Design: A multicenter, pilot study, for radiological assessment of thoracolumbar spine fractures was performed with the participation of 7 centers in Africa, Europe, Asia, and South America as a part of the AO Foundation network. Objectives: To determine the interobserver variability for computed tomography (CT) scan–based evaluation of posterior ligament complex (PLC) injury in thoracolumbar fractures. Methods: Forty-two observers including 1 principal investigator at each participating center performed variability assessment. Each center contributed toward a total of 91 patient images with A3 or A4 thoracolumbar burst fractures (T11-L2) with or without suspected PLC injury. Pathological fractures, multilevel injuries, obvious posterior bony element injury and translation/dislocation injuries were excluded. Ten patients were randomly selected and commonly reported CT parameters indicating PLC injury, including superior inferior endplate angle, vertebral body height loss, local kyphotic deformity, interspinous distance and interpedicular distance were assessed for variability. Observer values were compared with an experienced gold rater in spinal trauma. Analysis of variability was performed for all observers, between the principal investigators and also between observers participating in each center. Results: The studied parameters showed considerable variability in measurements among all observers and amongst all participating centers. The variability between the principal investigators was lower, but still substantial. The deviation of observer measurements from the gold rater were also significant for all CT parameters. Conclusions: CT-based radiological parameters previously reported to be suggestive of PLC injury showed considerable variability and magnetic resonance imaging verification of a PLC injury in all doubtful cases is suggested.